PENGARUH KEMASAN PRODUK MINUMAN COKLAT BANJAROYO TERHADAP MINAT BELI - Diklusari Isnarosi Norsita; Ika Restu Revulaningtyas; Sri Wijanarti (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The development of ready-to-drink chocolate products is a milestone to increase the added value of cocoa beans. Cocoa bean is a potential commodity of Banjaroyo, Kulon Progo Regency, DIY. The development of chocolate beverage needed ability of producers to understand consumer demand, including in terms of product appearance, so the products can be accepted in the market. This study aimed to analyze the effect of packaging of Banjaroyo chocolate beverage on buying interest. Product packaging attributes that will be examined were colors, illustrations, forms, information and typography. This study used a quantitative approach by collecting assessments of 100 respondents and qualitative data as a support. The level of influence of packaging attributes on consumer buying interest was analyzed by regression tests and descriptive analysis. The results showed that the packaging color, illustrations, forms, information and typography simultaneously affected 66.4 % buying interest. The packaging form and packaging typography and information attributes significantly influence buying interest by 48.94 % and 10.74 %. Based on descriptive analysis respondents liked the form of a sturdy packaging, and easy to hold. However, packaging requires an improvement in the completeness of product information, and the uniqueness of the illustrations.